LINP1 facilitates DNA damage repair through non-homologous end joining (NHEJ) pathway and subsequently decreases the sensitivity of cervical cancer cells to ionizing radiation. Issue 4 (16th February 2018) - Wang, Xuanxuan; Liu, Hai; Shi, Liming; Yu, Xiaoli; Gu, Yanjun; Sun, Xiaonan
ABSTRACT: LncRNA in non-homologous end joining (NHEJ) pathway 1 (LINP1) is an lncRNA which promotes therapeutic resistance in triple-negative breast cancer (TNBC). However, the expression and function of LINP1 in cervical cancer is not yet well-understood. In this study, we evaluated the expression levels of LINP1 in tumor tissues and cell lines of cervical cancer. We found that LINP1 associates with NHEJ proteins (Ku80 and DNA-PKcs). LINP1 translocates from cytosol to nucleus in response to irradiation. In addition, LINP1 knockdown significantly increases the levels of cleaved caspase3 and PARP, leading to enhanced cell apoptosis after ionizing radiation (IR). LINP1-knockdown cells showed delayed repairs of DNA double-strand breaks (DSBs) after IR. Finally, LINP1 knockdown increases radiosensitivity of Hela S3 cells. These results suggest that LINP1 facilitates DSBs repair through NHEJ pathway and may thus serve as a prognostic marker and a potential target for the therapy of cervical cancer.